ACADEMIC PERFORMANCE IN THE DIGITAL AGE: THE ROLE OF SOCIAL MEDIA AMONG UNIVERSITY STUDENTS - K. Ebiraj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Technology has emerged and penetrated in the form of internet and the advancements that it brings about with it. Social media is being used by students as one of the communication tools to interact, to read, to get themselves informed etc. In India and the globe today, social media has gained sufficiency and has become a instrument for communication and social unity surrounded by students. Many research studies has revealed that social media being a powerful tool can influence and shape individual and mass behavior progressively. The use of this multiplicity of social media has assorted effects on the user’s life, some of which are negative and others, positive. The study determined on three key impact areas: The time spent on social media, the frequency of visiting social media and the association between the volume of social media friends and a student’s academic performance. The study adopted a paper-based open ended and close-ended questionnaire and was restricted to University students. The proposed research study envisioned to study the academic impact of social media among the University students of Bangalore and Chennai for which research engages quantitative research approach to answer the research questions of the study.